Digitisation of MSMEs Payments for Dodol Nangka Through the Implementation of QRIS - Alya Riskia; Ali Akbar Hidayat; Baiq Anita Anhapia; Aulia Putri; Baiq Indira Laila F; Elsa Aza; Genta Aditya Zamzamy; Muh Indra Jayadi; Isnada; Lalu Zulkifli; Lalu Zuhdi Jati F; Lisa Ramdayani; Lisnawati; Muhammad Daiadin; Niswatun Afifa; Azhrina; Siti Saadah; Suci Hartini; Ni Widyarsini; Yauma Fashia F; Yulia Anggraeni; Yuka Gustina; Aghnia Amaliatus Shalihah; Vici Handalusia Husni; Wahidin; Tuti Handayani (Unram Journal of Community Service, 2026)
The development of the digital economy requires Micro, Small and Medium Enterprises (MSMEs) to adapt to modern and efficient payment technologies. This project aims to assist MSMEs selling dodol nangka (jackfruit dodol) in implementing QRIS (Quick Response Code Indonesian Standard) as a cashless payment system. Through the application of QRIS, the transaction process becomes faster, safer and more practical for both consumers and businesses. The stages of the activity include socialising the use of QRIS, registering business accounts, and creating and installing QRIS codes at points of sale. The results of this activity show that the use of QRIS can increase transaction efficiency, reduce dependence on cash, and expand market access for dodol nangka MSMEs. Thus, the implementation of QRIS is a strategic step to encourage digital transformation and support the realisation of a cashless economy at the local level.